1985
DOI: 10.1063/1.95883
|View full text |Cite
|
Sign up to set email alerts
|

Absence of oxygen diffusion during hydrogen passivation of shallow-acceptor impurities in single-crystal silicon

Abstract: It was recently proposed that hydrogen compensation of shallow-acceptor impurities in single-crystal silicon is due to the diffusion of both monatomic oxygen and hydrogen into silicon which combine at acceptor sites to form neutral acceptor-OH complexes. It is shown here that oxygen does not diffuse into silicon under the conditions of shallow-acceptor passivation. Boron-doped silicon was exposed to monatomic deuterium and mass 18 oxygen at elevated temperatures. Depth profiles of D and 18O were measured by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(21 citation statements)
references
References 10 publications
3
15
1
Order By: Relevance
“…The discrepancies with other measurements between 500-900 K, [2][3][4] where much lower diffusion coefficients were found, can be attributed to trapping effects. 25 In particular, this applies to all previous experiments using ion implantation: Lanford et al 26 and Whitlow et al 27 implanted 10 16 1 H/cm 2 at 7.5 and 25 keV, respectively, and Fink et al 28 10 15 -10 17 1 H/cm 2 at 100 keV.…”
Section: A High Temperature Regimecontrasting
confidence: 89%
“…The discrepancies with other measurements between 500-900 K, [2][3][4] where much lower diffusion coefficients were found, can be attributed to trapping effects. 25 In particular, this applies to all previous experiments using ion implantation: Lanford et al 26 and Whitlow et al 27 implanted 10 16 1 H/cm 2 at 7.5 and 25 keV, respectively, and Fink et al 28 10 15 -10 17 1 H/cm 2 at 100 keV.…”
Section: A High Temperature Regimecontrasting
confidence: 89%
“…The H atom loses electrons to the surface rather than gain electrons as in the LDA results, though the main character of the energy curves are still retained. That the H atom prefers to lose electrons in the silicon bulk was already reported by the experimental studies for the behavior of the H atom in the p-type silicon (e.g., Johnson and Moyer [8]). …”
Section: Introductionsupporting
confidence: 58%
“…5(d)]. That H atom tends to lose electrons in the silicon bulk was already reported by the experimental studies for the behavior of the H atom in the p-type silicon [8].…”
Section: Hydrogen Atom Approaches Si(111)(1 × 1) Surfacementioning
confidence: 62%
“…Hydrogen was implicated by both groups as the cause for the removal of free holes in the p-type silicon. Secondary ion mass spectrometry (SIMS) of deuterium RF plasma exposed p-type silicon wafers showed that the acceptor and the deuterium concentrations were identical in the deactivated region (13). The deactivation of acceptors by another impurity immediately reminds us of the well known lithium compensation and passivation of acceptors in Si and Ge (14).…”
Section: Neutral Shallow Acceptor-and Donor-hydrogen Complexesmentioning
confidence: 93%